Efektifitas Pelaksanaan Corporate Governance dan Audit Eksternal Auditor dengan Spesialisasi Industri dalam Menghambat Manajemen Laba - Antonius Herusetya (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2009)
The purpose of this study is to examine whether the principle of corporate governance is practiced effectively by the public listed companies, and has the ability to reduce agency cost from opportunistic earnings management. With the sample of 115 firms years in the year 2005 and 2006 from public companies audited by The Big 4 and non- Big 4 auditors, we haven’t yet provide any evidence that the practice of corporate governance (reflected by the Corporate Governance Performance Index- CGPI 2005) could reduce the possibilities of earnings management. We conduct other alternative tests using the monitoring mechanism and independency of the Board of Commissioners, and give the same result with the above tests. While in our other tests using the external audit- one of the functions of the gatekeeper of capital market, The Big 4 auditors (both with and without industry specialization) and non- Big 4 auditors could not provide any evidence that these gatekeepers functioned effectively to detect opportunistic earnings management. In other words, there is no difference whether these public companies audited by The Big 4 auditors, non- Big 4 auditors or even The Big 4 auditors with industry specialization. The result of this study regarding the practice of corporate governance and audit quality in the context of Indonesia is still questioned and unsolved. Cahan et al. (2008) found evidence that countries with weak investor protection have lower corporate governance quality compared to countries with stronger investor protection. That evidence might explain why corporate governance practice measured by CGPI 2005, and other alternative mechanism tests done by us could not described the above results.Keywords: corporate governance, external audit, The Big 4 auditors, earnings management, industry specialization, board of commissioners